Malaria prevalence and mosquito net coverage in Oromia and SNNPR regions of Ethiopia - WeldeMeskel Asrat; Olana Dereje; Endeshaw Tekola; Ejigsemahu Yeshewamebrat; Emerson Paul M; Mosher Aryc W; Graves Patricia M; Ngondi Jeremiah; Gebre Teshome; Shargie Estifanos B; Teferra Admas; Tadesse Zerihun; et al. (BMC, 2008)
Abstract Background Malaria transmission in Ethiopia is unstable and seasonal, with the majority of the country's population living in malaria-prone areas. Results from DHS 2005 indicate that the coverage of key malaria interventions was low. The government of Ethiopia has set the national goal of full population coverage with a mean of 2 long-lasting insecticidal nets (LLINs) per household through distribution of about 20 million LLIN by the end of 2007. The aim of this study was to generate baseline information on malaria parasite prevalence and coverage of key malaria control interventions in Oromia and SNNPR and to relate the prevalence survey findings to routine surveillance data just before further mass distribution of LLINs. Methods A 64 cluster malaria survey was conducted in January 2007 using a multi-stage cluster random sampling design. Using Malaria Indicator Survey Household Questionnaire modified for the local conditions as well as peripheral blood microscopy and rapid diagnostic tests, the survey assessed net ownership and use and malaria parasite prevalence in Oromia and SNNPR regions of Ethiopia. Routine surveillance data on malaria for the survey time period was obtained for comparison with prevalence survey results. Results Overall, 47.5% (95% confidence interval (CI) 33.5-61.9%) of households had at least one net, and 35.1% (95% CI 23.1-49.4%) had at least one LLIN. There was no difference in net ownership or net utilization between the regions. Malaria parasite prevalence was 2.4% (95% CI 1.6-3.5%) overall, but differed markedly between the two regions: Oromia, 0.9% (95% CI 0.5-1.6); SNNPR, 5.4% (95% CI 3.4-8.5), p < 0.001. This difference between the two regions was also reflected in the routine surveillance data. Conclusion Household net ownership exhibited nearly ten-fold increase compared to the results of Demographic and Health Survey 2005 when fewer than 5% of households in these two regions owned any nets. The results of the survey as well as the routine surveillance data demonstrated that malaria continues to be a significant public health challenge in these regions-and more prevalent in SNNPR than in Oromia.